1995
DOI: 10.1523/jneurosci.15-12-08023.1995
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of olfactory learning by a modulator of AMPA receptors

Abstract: The effects of a benzoyl-piperidine drug (BDP) that facilitates AMPA receptor-mediated synaptic responses were tested on the acquisition and retention of long-term memory at dosages that had no detectable effects on a variety of performance measures. BDP-12 produced a dose-dependent suppression of exploratory activity in rats with statistically reliable effects occurring at 50 mg/kg (i.p.). The drug had no effects on balance beam performance at 30 mg/kg but at 45 mg/kg reduced the number of crossings made with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 20 publications
5
44
0
Order By: Relevance
“…AMPA receptor modulators that alter receptor kinetics may influence long-term potentiation, long-term depression (22)(23)(24), and various forms of memory function in both animals (23,25,26) and humans (27,28). Mice with either a GRIA1 or GRIA3 gene deletion showed significant changes in hippocampal long-term potentiation (18,29).…”
Section: Discussionmentioning
confidence: 99%
“…AMPA receptor modulators that alter receptor kinetics may influence long-term potentiation, long-term depression (22)(23)(24), and various forms of memory function in both animals (23,25,26) and humans (27,28). Mice with either a GRIA1 or GRIA3 gene deletion showed significant changes in hippocampal long-term potentiation (18,29).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were trained on a series of ten novel discriminations over successive days until they showed a strong preference for the positive cue in trials 6-10. Past work showed that such learning results in long-term memory (Larson et al 1995). A novel odor pair was presented on the test day.…”
Section: Lpp-dependent Learning Induces Lppltpmentioning
confidence: 99%
“…Animal experiments have also demonstrated that ampakines improve performance in a variety of memory tasks like odor discrimination (Larson et al, 1995;Staubli et al, 1994a), spatial mazes (Granger et al, 1993;Staubli et al, 1994a), a spatial delayed-non-match-to-sample task (Hampson et al, 1998), eye-blink conditioning (Shors et al, 1995) and learned fear (Lebrun et al, 2000). Ampakines have also been shown to be effective in reducing age-associated memory deficits in rats .…”
Section: Introductionmentioning
confidence: 99%